Tuneable Fiber Bragg Grating for Magnetic Field Sensor - Al-Thahaby, Farah S.; Al-Dergazly, Anwaar A. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this work, four fiber Bragg gratings are fabricated by infiltration different volumes of liquids (star line Glass Mechanix optical adhesive material, olive oil diluted with ?ethanol) into the hollow core photonic crystal fibers (HC19-1550 (Thorlab Company)). The amplitude splitting interferometric technique with a high resolution specially designed translation stage was used for the fabrication process. This stage is capable of moving the fibers in micrometer ?resolution steps. The fabrication was carried out using blue laser operated at wavelength of 405 nm. The infiltrated four photonic crystal fibers were exposed to the blue laser beam of 405 nm forming periodic fringes for Bragg grating generation. These fringes were generated from the interference of two splitted laser beams. All fabricated fibers have the same Bragg length of 3.8 cm and average gratings periods of 0.224 ?m. The four fibers were analyzed by an optical microscope which displayed the areas that were cured using blue laser. The fabricated fibers also were tested by putting laser beam at one end of the fiber and determining the transmittance at the other fiber end by optical signal analyzer? (Thorlabs-CCS200). The resulted Bragg grating fibers have 653.3 nm Bragg reflected wavelength. The results also showed that fiber with higher volume of olive oil has the highest reflection peak about ?96.09647 %? with the greatest FWHM (full width at a half maximum) ?about 0.74 nm.In addition, three of the fabricated fibers (B, C and D) that contained olive oil were prepared for testing magnetic field sensor. The results show that all the fibers shifted to near infrared range. The results also showed that fiber with higher concentration of olive oil has the greatest magnetic wavelength shift about 653.4 nm, the highest fiber sensitivity about ??0.000494623656 nm/ Gauss?, the highest reflection peak about 96.91827? %, and the greatest FWHM ?about 0.98 nm.